USE OF PSEUDOMONAS PUTIDA AND PANTOEA AGLLOMERANS AS PHOSPHORUS SOLUBILIZING BACTERIA IN OXISOL - Junior Barbosa, Denner; Gentil, Kevin (Journal of Interdisciplinary Debates, 2023)
largest biome in total area in South America, this biome has great aptitude for agriculture and stands out every year in the production of agricultural commodities in the national territory, being consolidated as the largest producer of soy, corn, cotton and the largest cattle herd in the world. country. However, it is worth mentioning that there is a limiting factor for production in the cerrado, which is the low natural fertility of its main type of soil, these soils with intense weathering are strongly acidic, have low saturation of bases and predominance of iron and aluminum oxides that adsorb phosphates. The objective of this work was to evaluate the efficiency of the bacteria Pseudomonas putida and Pantoea agglomerans, present in the commercial product Phospho Bavar-2, as potential phosphorus solubilizing bacteria (BSP) in latosols, acting in the conversion of non-labile phosphorus into forms readily available to plants. . The experiment was carried out from 03/11/2019 to 04/03/2020 at the experimental farm of IFMT Campus Sorriso in red yellow latosol. The treatments consisted of different doses of triple superphosphate in seeds treated with the bacteria Pseudomonas putida and Pantoea agglomerans, present in Biofertilizante BARVAR-P-2® from Green Biotech Brasil. The treatments were: T1 (Without inoculant+100% fertilizer dose), T2: (With inoculant+100% fertilizer dose), T3: (With inoculant+50% fertilizer dose), T4 (Comm inoculant+0% fertilizer dose), T5: (Without inoculant+50% fertilizer dose), T6: (Without inoculant+0% fertilizer dose). There was no significant interaction between inoculant use and productivity in Kg/Ha-1. However, when comparing the productivity averages achieved in the experiment with productivity data at regional and national level, it is possible to verify satisfactory averages that may be directly related to the use of the product.